Farm-level modelling of bioeconomic, greenhouse gas emissions and feed-food performance of pasture-based dairy-beef systems. (December 2022) - Kearney, M.; O'Riordan, E.G.; McGee, M.; Breen, J.; Crosson, P.
Abstract: CONTEXT. Global demand for grass-based beef systems is increasing with a growing proportion of beef output in many countries originating from the dairy herd. Concurrently, concerns around the environmental impact of food, particularly that derived from ruminants, and food security is growing in prominence. Therefore, a comprehensive analysis of the sustainability of dairy-beef systems is required. OBJECTIVES: The objectives of this study were to (1) augment an existing farm-level bioeconomic model to permit greenhouse (GHG) emissions and feed-food analysis of dairy-beef systems and (2) use this model to asses the performance of grass-based dairy-beef steer production systems. METHODS: The developed farm-level model was used to evaluate production systems finishing males as steers on three contrasting soil types and differing with respect to sire breed (early-maturing, late-maturing and dairy), age at slaughter (20, 24 and 28 months of age) and finishing diet (grazed grass or grass silage, each supplemented with concentrates). RESULTS AND CONCLUSIONS: Results highlighted a wide range in farm net margins (from €134 to €515 per hectare) with systems finishing off pasture in the second grazing season being most profitable. These systems also had lowest GHG emissions intensities. Steer systems finishing off pasture during the third grazing season were the only net producers of human-edible protein, whilst all systems were net consumers of human-edible energy. Production systems on higher quality land were more profitable, had lower GHG emissions but used more tillable land than systems on poorer quality land. SIGNIFICANCE: Under the conditions modelled in this study, inverse relationships were found between system profitability, human-edible protein and energy efficiency and greenhouse gas emissions implying trade-offs may need to considered in respect of sustainability metrics. Graphical abstract: Unlabelled Image Highlights: A growing proportion of global beef output is from the dairy herd and therefore, sustainability analyses of these systems are required. Grass-based dairy-beef steer systems differing in respect of breed, age at slaughter and finishing diet were modelled for three land types. Steers slaughtered in the second grazing season were most profitable and had lowest GHG emissions per kilogram of beef. Steer systems finishing during the third grazing season were the only net producers of human-edible food and only in the context of protein food. Dairy-beef systems on higher rather than poorer quality land were more profitable, had lower GHG emissions but used more tillable land.